Hydrometallurgy '94 proceedings... - London.Institute of Mining and Metallurgy and the Society of Chemical Industry; International Symposium on Hydrometallurgy Cambridge 11 - 15 July 1994; London.Institute of Mining and Metallurgy and the Society of Chemical Industry (London Chapman and Hall, 1994)
Hydrometallurgy '94 contains the 78 papers that were presented at the international symposium organized by the Institution of Mining and Metallurgy and the Society of Chemical Industry and held in Cambridge, England, in July 1994. In the papers specific attention is paid to the concept of sustainable development and the associated ideas of cleaner technology, recycling and waste minimization that have particular relevance to the extractiona nd processing of metals and other mineral products. The papers, by authors from 30 contries, are grouped under the headings: Hydrometallurgy and Sustainable Development; Materials Production and the Environment; Fundamentals; Leaching; Bioprocessing; Gold Solution Purification; Effluent Treatment; Processes; and Recycling.
Keywords: Hydrometallurgy; Hydraulic engineering